[P298] The influence of variations of the beam quality for high energy photon beams on tissue inhomogeneity correction factors for radiotherapy treatment plans. (August 2018) - Akhtaruzzaman, Md; Kukołowicz, Paweł Franciszek
Abstract : Purpose: The purpose of this study was to assess the effect of variations of the beam quality (TPR20, 10 ) for photon beams on tissue inhomogeneity correction factors (ICFs). Methods: A total of 90 three-dimensional conformal radiotherapy (3DCRT) treatment plans for three locations (3DCRT lung, gynaecological, prostate) and 15 SRS lung plans were considered for this study. For 3DCRT plans, the ICFs were calculated for a range of beam qualities. For 6 MV, the range of TPR20, 10 was 0.670 ± 3%, and for 15 MV, the range of TPR20, 10 was 0.760 ± 3%. The stereotactic plans were prepared with two 6 MV beams from a Varian TrueBeam accelerator - one generated with a flattening filter (X6, TPR20, 10 = 0.688) and one flattening filter free (X6FFF, TPR20, 10 = 0.632). Calculations were performed using Eclipse treatment planning system (TPS) with the anisotropic analytical algorithm (AAA). ICFs were also measured in a CIRS Tissue Simulation Phantom (thorax with lungs) for two fields 5 × 5 and 10 × 10 for X6 and X6FFF beams. PTW Farmer and semiflex ionization chambers were used for measurements. Results: Calculations for 3DCRT plans showed that the 6% variations in energy (TPR20, 10 ) lea to average changes of ICFs of 2.0% (6 MV) and 2.6% (15 MV) for lung cases. For gynaecological and prostate patients, the mean differences of ICFs were less than 1%. The difference of 5.6% of TPR20, 10 values between X6 and X6 FFF for lung SRS treatment plans led to a difference of ICFs of less than 2%. Measurements with the CIRS phantom also demonstrated differences of ICFs consistently less than 5% between X6 and X6 FFF beams. Conclusions: The influence of energy on inhomogeneity correction factors is rather small. Correction factors measured on one accelerator may be used for another accelerator with similar energy provided quality control tests are performed.